Implementation of K-Nearest Neighbor (KNN) algorithm for detection of QRS Complexes - Mathur, P; Chouhan, V S (International Journal of Computer Sciences and Engineering, 2018)
In this paper, K-Nearest Neighbor (KNN) algorithm as a classifier is implemented with slope as feature for detection of QRS-complex in ECG, the detection rate of 99.32% is achieved. The proposed algorithm is evaluated on standard databases CSE dataset-3.